A Deep Learning Approach to Optimal Sampling Problems. (16th June 2022) - Wang, Xinxin; Meng, Xiangyu; Li, Fangfei
Abstract : Time-triggered and event-triggered sampling methods have been widely adopted in control systems. Optimal sampling problems of the two mechanisms have also received great attentions. However, for high-dimensional systems, analytical methods have some limitations. In this study, we propose a model-free method, called soft greedy policy for neural network fitting, to calculate the optimal sampling period of the time-triggered impulse control and the optimal threshold of the event-triggered impulse control. A neural network is used to approximate the objective function and then is trained. This approach is more widely applicable than the analytical method. At the same time, compared with different ways of generating data, the algorithm can carry out real-time update with greater flexibility and higher accuracy. Simulation results are provided to verify the effectiveness of the proposed algorithm.